On the solvability of the nonlinear problem for elliptic-parabolic system of the equations in Hölder spaces - Bizhanova, G.I. (Нелинейные граничные задачи, 2004)
There is proved the existence and the uniqueness of the solution of the nonlinear H.Amann problem for the parabolic-elliptic equations for the small time in the Holder spaces, the estimates for the solution are derived, the smoothness on t of the potential φ is obtained.